Extremophilic cyanobacteria from thermo-mineral springs of spas in Atlantic environments. Issue 1 (31st December 2022) - López-Rodríguez, M. Carmen; Asencio, Antonia D.; Meijide, Rosa M.; Torres, Enrique
Abstract : The species composition of cyanobacteria assemblages was studied in six thermo-mineral springs of spas in Atlantic environments of Galicia (NW Spain). Two are considered hot (T a ≥ 40 °C), two intermediate (T a 20–40 °C) and two cold (T a ≤ 20 °C), and four contain hydrogen sulphide. A total of 21 taxa (14 genera) have been recorded. Two diversity indices, Shannon index and Evenness were determined. The Shannon–Wiener index ranged between 0.31 and 0.73 and the Evenness index between 0.44 and 0.88. nMDS ordination showed that cyanobacteria assemblage composition was influenced mostly by temperature. Of the species identified, the most diverse genus is Leptolyngbya with four species, followed by Chroococcus with three species and Aphanocapsa, Phormidium and Lyngbya with two species. The most abundant species was Jaaginema angustissimum, followed by Leptolyngbya laminosa and Symploca thermalis. In the two cold springs, seven different species were found, and only Aphanocapsa conferta was common to both springs. Cyanobacterial species were more numerous in the four hot springs, with 15 different species and only Calothrix thermalis common to these hot springs. It is difficult to establish characteristic cyanobacterial flora for the thermo-mineral waters of the Galician springs since there are significant differences in the communities from the six sites studied.